Pengembangan Media Video Animasi pada Metode Inkuiri untuk Pembelajaran IPS Kelas IX SMP - Khairunnisa Khairunnisa; Darmansyah Darmansyah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
One effort that can be done to solve problems in learning is to develop learning media on the right method. One of the learning problems found was the lack of student interest in learning social studies because the methods and media used were not appropriate. Social studies learning has a lot of material descriptions and contains abstract things if delivered using methods that cannot involve students in learning and media that are less attractive, it will make students less enthusiastic to learn. Therefore, this development research aims to produce an animated video product on the inquiry method for social studies learning for Class IX SMP that is valid, practical and feasible. This research uses a type of development research or also known as Research and Development (R&D). The development model used is the ADDIE model. The ADDIE model consists of five stages of development, namely: (1) Analysis (Analysis), (2) Design (design), (3) Development (development), (4) Implementation (application), (5) Evaluation (evaluation). Products in the form of animated video media will be tested for the validity of the media by two validators and the validity of the material will be tested by one validator. Practicality test was conducted on 21 students of class IX. 4 at SMPN 1 Tanjung Raya. Based on the results of the product validity test, it shows that the media is said to be very valid with a proportion of 92.06%, according to the proportion of experts who are right at 90%. In the final results of the practicality test of learning media products, it is categorized as very valid with a percentage of 92.38%. In accordance with these results, it can be said that the learning animation video media on the inquiry method for social studies learning for class IX SMP is declared valid; practical and feasible to use.